2020
DOI: 10.1038/s41467-020-19935-y
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitination of RIPK1 regulates its activation mediated by TNFR1 and TLRs signaling in distinct manners

Abstract: RIPK1 is a death-domain (DD) containing kinase involved in regulating apoptosis, necroptosis and inflammation. RIPK1 activation is known to be regulated by its DD-mediated interaction and ubiquitination, though underlying mechanisms remain incompletely understood. Here we show that K627 in human RIPK1-DD and its equivalent K612 in murine RIPK1-DD is a key ubiquitination site that regulates the overall ubiquitination pattern of RIPK1 and its DD-mediated interactions with other DD-containing proteins. K627R/K612… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 60 publications
0
27
0
Order By: Relevance
“…Under the stimulation of TNF- α , TNFR1 was a powerful proinflammatory cytokine that participates in the occurrence of various inflammations and degenerative diseases [ 33 ]. RIPK1-DD-mediated dimerization was the key to promote the activation of RIPK1 during the process of tumor necrosis factor- α -stimulated cell transition from complex I to complex II [ 34 ]. In addition, the potential crucial genes need further validation by RT-qPCR in clinical samples.…”
Section: Discussionmentioning
confidence: 99%
“…Under the stimulation of TNF- α , TNFR1 was a powerful proinflammatory cytokine that participates in the occurrence of various inflammations and degenerative diseases [ 33 ]. RIPK1-DD-mediated dimerization was the key to promote the activation of RIPK1 during the process of tumor necrosis factor- α -stimulated cell transition from complex I to complex II [ 34 ]. In addition, the potential crucial genes need further validation by RT-qPCR in clinical samples.…”
Section: Discussionmentioning
confidence: 99%
“…JMJD3 mediated H3K27me3 demethylation is a critical repressive epigenetic event, which exerts functions in multiple physiological and pathological processes [ 33 , 34 ]. Although previous study have shown that JMJD3 deeply involved in the neurogenesis and neurodegeneration of CNS, as cellular responses to SCI, the underlying epigenetic motivations of JMJD3 fluctuation still to be further investigated [ 34 , 35 ]. From the pathological gliogenesis perspective, the overwhelming majority of newly generated cells in response to SCI are reactive astrocytes [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, RIPK1 regulates the extrinsic apoptosis pathway by interacting with the death domains of FADD and TRADD in DISC [153,158,174,175]. The effects of RIPK1 are further regulated via PTM through the NFκB-mediated pathway or independently of NFκB [176,177]. Recently, Smyth et al introduced FLIP(L) as a pseudocaspase, which has structural homology with caspases 8 and 10 in its C terminal; however, this homology domain in FLIP(L) lacks catalytic function.…”
Section: Tumor Necrosis Factor Receptor (Tnfr)mentioning
confidence: 99%